Treating patella fractures with a locking patella plate - first clinical results. (June 2018) - Wurm, Simone; Bühren, Volker; Augat, Peter
Abstract: The standard treatment for patella fractures is tension band wiring. However, with tension band wiring anatomical reduction and rigid fixation can be challenging and the clinical outcome after patella fracture is often not satisfying. The purpose of this prospective clinical observation was to evaluate the clinical outcome in patients with patella fractures treated with an angular stable patella plate. Between 2011 and 2015 a total of 67 patients were treated with an angular stable patella plate. Outcome in these patients was evaluated by the Knee Outcome Survey Activities of Daily Living Scale (KOS-ADL) and range of motion of the knee joint was assessed. Complete follow up was obtained for 35 patients. In these patients, we found one implant-related complication. None of the patients reported any deficits in extension capabilities. The flexion was on average 127° (SD 21°). The patients classified the function of their knee in daily life on average with 77% (SD 24%) in comparison to their function before the trauma. Only kneeling or squatting was a problem in some patients. In conclusion, angular stable patella plating appears to be a promising alternative treatment for patella fractures. The patella plate provides increased mechanical stability for fracture fixation which appeared to result in a reduction of complications and improvement of functional outcome compared to tension band wiring. Especially patients with a multi-part or comminuted fracture or with osteoporotic bone are likely to benefit from the stability provided by the plate and the locking screws.